Marshall Characteristics Test on Asphalt Concrete Mixtures – Wearing Course Using Modified Asbuton - Toad, Wellem; Kabo, Don; Manginsihi, Barakati; Hosang, Merci (Jurnal Multidisiplin Madani, 2024)
Indonesia is a country rich in natural resources, one of which is natural asphalt found on Buton Island, Southeast Sulawesi, known as Buton asphalt (Asbuton). With the increasing development activities in Indonesia, the government is striving to reduce dependency on asphalt imports and optimize the utilization of Buton asphalt, particularly throughout Indonesia. Preblended Asbuton is a type of modified Buton asphalt that has begun to be widely used in various asphalt mixtures. This research aims to: (1) Obtain an optimal asphalt content (KAO) that is good and meets specifications; (2) Obtain Marshall characteristic values (Stability, Flow, VIM, VMA, VFB, density, and MQ) in the Asphalt Concrete - Wearing Course mixture using modified Buton asphalt (preblended) as a binder. Based on the research results, the Marshall characteristic values for the AC-WC Buton asphalt mixture are: VIM (Void in Mix) = 4.18%, VMA (Void Mineral Aggregate) = 16.80%, VFB (Void Filled With Bitumen) = 74%, density = 2.270 gr/cm³, Stability = 1400 kg, Flow = 3.350 mm, MQ (Marshall Quotient) = 410 kg/mm, KAO = 5.85%, and it meets the Asphalt Mixture Specifications with Buton Asphalt (Bina Marga Revision 1, 2018)